Effects of gas and other fume emitting heaters on the development of asthma during childhood. Issue 9 (27th August 2004) - Phoa, L L; Toelle, B G; Ng, K; Marks, G B
Abstract : Background: Several studies have shown adverse effects of gas cookers and heaters on respiratory health. The long term effects of early life exposure to these appliances are not known. This study investigated the effect of exposure to fume emitting heaters, currently and during the first year of life, on the risk of asthma outcomes. Methods: A cross sectional study of schoolchildren (n = 627) aged 8–11 years was conducted in Belmont, Australia. Information on symptoms and heating types was collected by parent completed questionnaire. Atopy was assessed by skin prick tests and airway hyperresponsiveness (AHR) was assessed by histamine challenge test. Results: There was no association between the current use of fume emitting heaters and any of the asthma outcomes. However, having been exposed to fume emitting heaters during the first year of life was associated with an increased risk of having AHR (relative risk (RR) 1.47, 95% confidence interval (CI) 1.06 to 2.03), recent wheeze (RR 1.44, 95% CI 1.11 to 1.86), and recent wheeze + AHR (RR 2.08, 95% CI 1.31 to 3.31). Conclusion: If confirmed in other settings, this finding would require a review of the range of heating types that are appropriate for use in households in which young children live.